Scaffold with Micro/Macro‐Architecture for Myocardial Alignment Engineering into Complex 3D Cell Patterns. Issue 22 (10th October 2019) - Zhang, Wanqi; Wang, Zuyong; Xie, Chao; Wang, Xianwei; Luo, Fangfang; Hong, Minghui; Zhou, Rui; Ma, Chao; Lin, Nan; Zhang, Jieyu; Hu, Xuefeng; Chan, Jerry Kok Yen; et al.
Abstract: Tissue structural anisotropy is an important basis for heart function. Attempts to regenerate the complicated heart‐tissue alignment has rarely featured macroscale 3D constructs required for myocardial tissue engineering. The feasibility of engineered scaffolds with micro/macro‐architecture for guiding spatial cell alignment following complex patterns is reported. The scaffold is composed of stackable dual‐structured layers with linear micro‐ridge/groove patterns and macro‐through‐hole arrays, which enable tailorable anisotropy and interconnective free space. When human mesenchymal stem cells are seeded on the scaffold, well‐organized spreading alignment showing the precise control in cellular orientation is significantly introduced over nonpatterned controls. Moreover, spatial cell distribution in the scaffold and directional changes of the layered linear patterns that made cell alignment orientations turning accordingly are observed, leading to the complex 3D pattern reconstruction of cellular alignment resembling natural myocardial tissue. This work validates the potential of micro/macro‐architecture engineering for spatial cell guidance. Scaffolds with this capability can be potentially used for biomanufacturing of the structural alignment in myocardial tissue engineering. Abstract : A scaffold with micro/macro‐architecture that mimics anisotropy in myocardial tissue can be obtained by using polymeric single‐axial drawing and direct laser perforation. Human mesenchymal stem cells can recognize the micro/macro‐architecture and align with cellular extension at controlled directions. This cellular alignment can be tailorable to form complex 3D structural patterns similar to natural myocardium. The scaffold micro/macro‐architecture engineering holds great potential in heart‐tissue‐structure reconstruction applications.